Learner Beliefs and Language Proficiency in SA Context: A Case study of Chinese Students Taking Pre-sessional Language Course in the UK - Li Xin; Zhang Jiayi (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2017)
This study seeks to explore the interrelation between learners’ beliefs and language proficiency in study abroad (SA) context. The participants of this study consisted of 30 Chinese students who were taking the pre-sessional language course at the University of Sheffield in the UK. Combining data from the questionnaires, semi-structured interviews and test scores, the current study tries to answer three research questions: (1) Do learners’ beliefs change in the SA context? If so, in what ways? (2) Does learners’ language proficiency change in the SA context? If so, in what ways? (3) What is the relationship between learners’ English language proficiency and their beliefs about language learning?By investigating learners’ beliefs change in SA context and how such change impacts on their language learning behavior and outcomes, it is hoped that students can have a more fruitful study-abroad sojourn.